Humoral and Cellular Response to Spike of Delta SARS-CoV-2 Variant in Vaccinated Patients With Multiple Sclerosis - Petrone, Linda; Tortorella, Carla; Aiello, Alessandra; Farroni, Chiara; Ruggieri, Serena; Castilletti, Concetta; Meschi, Silvia; Cuzzi, Gilda; Vanini, Valentina; Palmieri, Fabrizio; Prosperini, Luca; Haggiag, Shalom; et al. (Frontiers in Neurology, 2022)
Objectives. We assessed vaccination-induced antibody and cellular response against spike from the ancestral strain and from the Delta SARS-CoV-2 variant in patients with Multiple Sclerosis (MS) treated with disease modifying treatments. Methods. We enrolled 47 MS patients and 9 controls (“no MS”) having completed the vaccination schedule within 4-6 months from the first dose. The Interferon (IFN)-γ-response to spike peptides derived from the ancestral and the Delta SARS-CoV-2 were measured by ELISA. Anti-Receptor Binding Domain (RBD) IgG were also evaluated. Results. No significant differences were found comparing the IFN-γ-specific immune response between MS and “no MS” subjects to the ancestral (p= 0.62) or Delta peptide pool (p=0.68). Nevertheless, a reduced IFN-γ-specific response to the ancestral or to the Delta pools was observed in subjects taking fingolimod or cladribina compared to subjects treated with ocrelizumab or IFN-β. The antibody response was significantly reduced in MS patients compared to “no MS” subjects (p=0.0452) mainly in patients taking ocrelizumab or fingolimod. Conclusions. Cellular responses to Delta SARS-CoV-2 variant remain largely intact in patients with MS. However, the magnitude of these responses depends on the specific therapy.